NRBF2 plays a crucial role in the acquisition process of learning and memory, independent of the Vps34 complex - Wu, Songfen; Zhuang, Haicai; Zhou, Xidan; Li, Kuan (Frontiers in Behavioral Neuroscience, 2025)
IntroductionNRBF2, a component of autophagy-associated PIK3C3/VPS34-containing phosphatidylinositol 3-kinase complex, plays a crucial role in learning and memory processes, yet its specific impact on memory and the underlying molecular mechanisms remains unclear.MethodsHere, we utilized NRBF2 knockout mice to examine its influence on the time course of fear memory. Employing quantitative PCR, Western blot analysis, behavioral tests, and electrophysiology, we investigated the mechanisms through which NRBF2 affects memory processing.ResultsWe observed an increase in Nrbf2 mRNA levels at 6 and 12 h, and protein levels at 6 h post fear conditioning. Depletion of NRBF2 impaired memory acquisition, short-term, and long-term memory without causing any anxiety-like behavior. Interestingly, inhibition of Vps34 and autophagy by SAR405 disrupted fear memory consolidation, while leaving memory acquisition, short-term memory, and long-term potentiation (LTP) unaffected. Our results suggested that NRBF2 deletion impaired memory acquisition through an autophagy-independent pathway and provided novel insights into the role of NRBF2 in the central nervous system.DiscussionThis study offer new insights into the role of NRBF2 and highlight the potential of targeting NRBF2 as a therapeutic strategy for addressing cognitive deficits associated with various disorders.